The Effectiveness of the Collaborative Learning Model in Improving Listening Skills of Eighth Grade Students at SMP Negeri 2 Pangsiden - Irmayani; Jamaluddin; Nuraini K (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study aims to determine the effect of the collaborative learning model on students' listening skills in the Indonesian language subject. The research approach used is quantitative with a quasi-experimental design. The population in this study consists of all eighth-grade students at a junior high school in Padang City, while the sample was selected using purposive sampling technique, namely class VIII A as the experimental class and class VIII B as the control class, each consisting of 30 students. The instruments used in this study include a listening skill test (pretest and posttest), an observation sheet for collaborative activities, and a student response questionnaire on collaborative learning. Data collection techniques were carried out through written tests, direct observations, and questionnaire distribution. The data were analyzed using descriptive statistics to assess the average pretest and posttest results, and inferential statistics using the independent t-test assisted by SPSS software. The results of the study show a significant improvement in students' listening skills in the class that applied the collaborative learning model compared to the class that used a conventional model. Based on these findings, it can be concluded that the collaborative learning model has a positive and significant effect on improving students' listening skills. Therefore, this model is recommended to be implemented as a learning strategy for Indonesian language subjects, particularly in developing listening skills among junior high school students.